Fabrication of bi-doped tio2 nanofibers for clean energy and water production under visible light - Chua, Song Cherng (2014)
The potential use of titanium dioxide (TiO2) for clean energy and water purification has been shown to tackle eminent world issues such as energy and water crisis extensively. However challenges remain as TiO2 possesses wide band gap that only allows limited photocatalytic activity under the renewable solar irradiation thus impeding the application of TiO2 to its fullest potential. Moreover, most photocatalytic H2 generation over TiO2 has been conducted under sacrificial condition using methanol, formic acid, glycerol and EDTA.